Mesenchymal stem cells therapy in children with end-stage kidney disease - Eka Laksmi Hidayati; Reza Fahlevi; Henny Adriani Puspitasari; Anisa Rahmadhany; Sudung Oloan Pardede (Paediatrica Indonesiana, 2022)
Chronic kidney disease (CKD) is a major health problem worldwide, with increasing incidence and prevalence. While the incidence of CKD in children is relatively low, CKD contributes to major health problems and has many long-term effects.1 Chronic kidney disease is characterized by a gradual decline in kidney function over time. The Kidney Disease Improving Global Outcomes (KDIGO) report defined CKD as an abnormality of renal structure or function with decreased glomerular filtration rate (GFR) that lasts more than three months. Chronic kidney disease is classified into 5 stages based on the GFR value.2 Patients with stage V CKD transition from progressive disease to irreversible, terminal, end-stage kidney disease (ESKD). To date, the standard of ESKD management has been kidney replacement therapy, consisting of hemodialysis (HD), peritoneal dialysis (PD), and/or kidney transplantation. Complexity and cost of kidney care have obvious consequences on the availability of kidney replacement therapy for children, especially in developing countries. Dialysis provides only partial replacement of renal functions, especially clearance and fluid balance, but does not cure the disease. Kidney transplantation is a curative management, but donor availability for pediatric patients remains challenging